2017
DOI: 10.1155/2017/5741948
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Genes Related to Inflammatory Bowel Disease Using Minimum Redundancy Maximum Relevance, Incremental Feature Selection, and the Shortest-Path Approach

Abstract: Identification of disease genes is a hot topic in biomedicine and genomics. However, it is a challenging problem because of the complexity of diseases. Inflammatory bowel disease (IBD) is an idiopathic disease caused by a dysregulated immune response to host intestinal microflora. It has been proven to be associated with the development of intestinal malignancies. Although the specific pathological characteristics and genetic background of IBD have been partially revealed, it is still an overdetermined disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 136 publications
0
24
0
Order By: Relevance
“…Supervised machine learning has already proved to be useful in disease diagnosis and prognosis as well as personalized medicine 13,14 . In IBD, machine learning has been used to classify IBD paediatric patients using endoscopic and histological data 15 , to distinguish UC colonic samples from control and Crohn's disease colonic samples 16 , and to discriminate between healthy subjects, UC patients, and Crohn's disease patients using transcriptional profiles of peripheral blood 17 .…”
Section: Ulcerative Colitis (Uc) Is One Of the Most Common Forms Of Imentioning
confidence: 99%
“…Supervised machine learning has already proved to be useful in disease diagnosis and prognosis as well as personalized medicine 13,14 . In IBD, machine learning has been used to classify IBD paediatric patients using endoscopic and histological data 15 , to distinguish UC colonic samples from control and Crohn's disease colonic samples 16 , and to discriminate between healthy subjects, UC patients, and Crohn's disease patients using transcriptional profiles of peripheral blood 17 .…”
Section: Ulcerative Colitis (Uc) Is One Of the Most Common Forms Of Imentioning
confidence: 99%
“…Accumulating evidence suggests that genetic factors are involved in the development of IBD ( 30 ). A total of 7 mutations within 4 genes were investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Then, using an SVM as a machine learning classifier, they identified a feature set containing 21 genes, which yield the highest prediction accuracy. Additionally, based on the concept of functional similarity among closely related proteins, the authors used the protein–protein interaction network of the proteins encoded by those 21 genes and applied the shortest path approach (typically defined as the path with the least number of links between two proteins in a network) to find an additional 20 candidate genes 41. In another interesting study by Isakov et al , novel candidate genes were identified by developing a machine learning model trained on expression values of known IBD susceptibility genes and their functional annotations.…”
Section: Role Of Machine Learning and Systems Biology In The Interprementioning
confidence: 99%